(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Worldwide birth defects are one of the main causes of morbidity and disability among children. The risk factors vary significantly by geography, depending on local environmental and genetic factors. Our aim was to ascertain the local risk factors for birth defects, which is the first step toward devising preventive policies. From February 2018 to October 2019, this case-control study was undertaken at Sir Salimullah Medical College and Mitford Hospital, Dhaka, in the Department of Neonatology and Obstetrics. During this period 49 admitted newborns with birth abnormalities were selected as cases, and children of similar gestational age, sex, and post-natal age were selected as controls for each case. To determine the risk factors for birth abnormalities, in-depth interviews with mothers regarding their demographic and obstetric histories were recorded and analyzed. We found that mothers aged 26-30 years had a significantly increased risk of birth defects (p = 0.01). Additionally, mothers who had a history of diabetes had a considerably higher risk of delivering a child with birth defects (p = 0.03). During the pregnancy period, mothers who attended <4 antenatal care (ANC) visits and mothers who did not take iron or folic acid supplementation had a higher risk of birth defects (p = 0.02 and p <0.01, respectively).We found out that the majority of birth defect risk factors are preventable or controllable. By promoting appropriate antenatal care and educating mothers about relevant regional risk factors, the occurrence of birth defects can be lowered significantly. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 33-39